APPROACHES TO ENHANCE ENGLISH SPEAKING SKILLS AMONG ENGINEERING GRADUATES THROUGH JAM SESSION IN A MIXED CLASSROO - Batool Fatima Khaleel, Dr. K B Glory, K Sree Vasudha, Md Shahida Sultana (International Journal of Advanced Science and Technology, 2020)
Communication skills are essential to increasing the employability of engineering graduates. It is observed that majority of engineering graduates lack speaking skills. Sufficient guidance should be provided to students in the direction of workplace communication. Thus, universities need to review the language and communication courses and teaching methods to reach and surpass the needs of all stakeholders. Therefore, taking these challenges into account, this paper focuses on the importance of English speaking skills among engineering graduates in a mixed classroom, and the challenges they face in both academic and professional life and their potential remedies. The pre-test and post-test were performed on 30 engineering students to assess their speaking ability levels. The findings indicate a substantial increase in their oral competency. The aim of the paper is to develop the oral competency of students through Impromptu or JAM session speaking activity.